Risk Assessment of Chemical Exposure through Consumption of Rainwater in Coastal Areas - Muhammad Syahrir; Sandi N. Sakaty; Herawati Herawati; Dwi Wahyu Balebu (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2026)
Coastal communities rely heavily on Rainwater as their main drinking water source, even though it can be contaminated with harmful chemicals such as nitrates, cadmium, fluoride, and lead. Prolonged exposure to these contaminants poses significant health risks, especially for vulnerable groups such as children and the elderly. This study aims to conduct a comprehensive health risk assessment of chemical exposure through rainwater consumption in coastal populations. An observational-analytical design was used, with the Environmental and Health Risk Assessment framework. The study population was divided into two groups: community and environmental samples. Rainwater samples were collected from eight shelter points, while 94 residents (children and adults) were selected as study subjects. Data collection was carried out through laboratory analysis and structured interviews. The Environmental and Health Risk Assessment methodology is carried out in four stages: hazard identification, dose-response analysis, exposure assessment, and risk characterization. The results showed that the concentration of chemical parameters (NO3, Cd, Pb, and F) in Rainwater was still within the permissible limits, indicating that Rainwater was relatively safe for consumption. The study provides important insights into the chemical risks associated with Rainwater, offering a foundation for targeted interventions to protect public health, strengthen resilience to environmental hazards, and ensure sustainable management of water resources. The results of the study show that the quality of Rainwater consumed by coastal communities is still within safe limits, but it still needs attention because prolonged exposure has the potential to cause health problems, the study also contributes to the existing literature by integrating chemical risk assessment into public health planning for vulnerable coastal populations, highlighting the importance of proactive risk management strategies in mitigating long-term health impacts.